Factors Affecting Job Motivation among Nurses at Punjab Institute of Cardiology, Lahore - Humaira Batool, Shazia Nazir, Nasim Rafiq, Zubaida Akhtar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim of study: The purpose of this study was to explore factors that affect motivation and demonization among nurses at Punjab institute of cardiology Lahore. Background: A lot of factors have an effect on the nurse’s concert point. Job contentment, organizational obligation, level of education, practices, nurse′s self-esteem, stress related to work and exhaustion, reinforce from workmates, sympathetic command, comments, guidance on quantifiable apparatus, acknowledgment, profession prospect, job surroundings, motivations, incentives, comprehension, skills promotions and capability stage are surrounded by the copious factors that affecting nurses concert. Method: Descriptive Cross Sectional Study. Place and duration of study: Punjab institute of cardiology Lahore, Pakistan were selected for study from October to December 2018. The data was collected from nurses at Punjab institute of cardiology Lahore. The sampling technique was used convenient sampling. Close ended (Likert scale) questionnaire was used to collect data. Data was analyzed SPSS version 23. Results: In overall performance 85% of nurse had good performance. 32.81% working in Punjab Cardiology were satisfied with Remuneration, Benefits and Recognition. Respondent 27.6% was not satisfied with availability of carrier advancement opportunities. Nurses were satisfied with work space and environment 39%. According to response rate satisfaction were reported work environment safe, infection control strategies available in every department of Punjab cardiology, pleasant temperature and all types of instruments available and in working condition. Conclusion: This study finding have implies that effort should be made in increasing mechanisms for proper exploitation of performance appraisal outcome and increasing courses tackle the knowledge and skill gap of nurses.